The first Lusaka upgrading and sites and services project summary of the main findings of a five-year evaluation - Bamberger, Michael; Sanyal, Bish; Valverde, Nelson (1981)
Two strategies addressed to the expanding population in squatter communities in Lusaka are the upgrading of existing dwelling units and the sites and services component which provided new housing to families in the higher income bracket. The project design offered avenues for high level community participation and involvement in the planning and implementation phases thereby reducing opposition to the project from any quarter. The project provided its clientele access to basic urban services, in addition to better quality housing. Its impact, however, on the families and national housing policy is still a question that has to be resolved.
Keywords: Public housing aspects -- Luzaka (Zambia); Low-income housing -- Lazaka (Zambia); Lusaka Housing Project Unit (Lusaka, Zambia); Housing finance